2022
DOI: 10.1002/ecy.3796
|View full text |Cite
|
Sign up to set email alerts
|

Foundational biodiversity effects propagate through coastal food webs via multiple pathways

Abstract: Relatively few studies have attempted to resolve the pathways through which the effects of biodiversity on ecosystem functioning cascade from one trophic level to another. Here, we manipulated the richness of habitat-forming seaweeds in a western Atlantic estuary to explore how changes in foundation species diversity affect the structure and functioning of the benthic consumer communities that they support. Structural equation modeling revealed that macroalgal richness enhanced invertebrate abundance, biomass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…
Loss of biodiversity has an impact on ecosystem functioning worldwide, but we lack an in-depth understanding of how this loss may influence ecosystem functions (EFs), such as primary productivity or soil and water processes, in the long term (Ramus et al, 2022).Many studies investigating the relationship between biodiversity and ecosystem functioning (BEF) have focused on the level at which biodiversity loss is critical to maintain a certain level of EF (Furey & Tilman, 2021;van der Plas, 2019). For example, it has been demonstrated that, in order to maintain EFs such as carbon sequestration or soil functioning to a high level of performance, species decline within an ecosystem must not exceed 20% (Newbold et al, 2016).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Loss of biodiversity has an impact on ecosystem functioning worldwide, but we lack an in-depth understanding of how this loss may influence ecosystem functions (EFs), such as primary productivity or soil and water processes, in the long term (Ramus et al, 2022).Many studies investigating the relationship between biodiversity and ecosystem functioning (BEF) have focused on the level at which biodiversity loss is critical to maintain a certain level of EF (Furey & Tilman, 2021;van der Plas, 2019). For example, it has been demonstrated that, in order to maintain EFs such as carbon sequestration or soil functioning to a high level of performance, species decline within an ecosystem must not exceed 20% (Newbold et al, 2016).
…”
mentioning
confidence: 99%
“…Loss of biodiversity has an impact on ecosystem functioning worldwide, but we lack an in-depth understanding of how this loss may influence ecosystem functions (EFs), such as primary productivity or soil and water processes, in the long term (Ramus et al, 2022).…”
mentioning
confidence: 99%